Chronic environmental circadian disruption increases atherosclerosis and dyslipidemia in female, but not male, ApolipoproteinE-deficient mice - Chalfant, Jeffrey M.; Howatt, Deborah A.; Johnson, Victoria B.; Tannock, Lisa R.; Daugherty, Alan; Pendergast, Julie S. (Frontiers in Physiology, 2023)
Shift work chronically disrupts circadian rhythms and increases the risk of developing cardiovascular disease. However, the mechanisms linking shift work and cardiovascular disease are largely unknown. The goal of this study was to investigate the effects of chronically shifting the light-dark (LD) cycle, which models the disordered exposure to light that may occur during shift work, on atherosclerosis. Atherosclerosis is the progressive accumulation of lipid-filled lesions within the artery wall and is the leading cause of cardiovascular disease. We studied ApolipoproteinE-deficient (ApoE-/-) mice that are a well-established model of atherosclerosis. Male and female ApoE-/- mice were housed in control 12L:12D or chronic LD shift conditions for 12 weeks and fed low-fat diet. In the chronic LD shift condition, the light-dark cycle was advanced by 6 hours every week. We found that that chronic LD shifts exacerbated atherosclerosis in female, but not male, ApoE-/- mice. In females, chronic LD shifts increased total serum cholesterol concentrations and with increased atherogenic VLDL/LDL particles. Chronic LD shifts did not affect food intake, activity, or body weight in male or female ApoE-/- mice. We also examined eating behavior in female ApoE-/- mice since aberrant meal timing has been linked to atherosclerosis. The phases of eating behavior rhythms, like locomotor activity rhythms, gradually shifted to the new LD cycle each week in the chronic LD shift group, but there was no effect of the LD shift on the amplitudes of the eating rhythms. Moreover, the duration of fasting intervals was not different in control 12L:12D compared to chronic LD shift conditions. Together these data demonstrate that female ApoE-/- mice have increased atherosclerosis when exposed to chronic LD shifts due to increased VLDL/LDL cholesterol, independent of changes in energy balance or feeding-fasting cycles.